Significado e impacto de la noción de contrato social en Rousseau y Kant. Alcances y limitaciones en la teoría democrática. (2012)
This article reviews some of the similarities and differences about the political and legal foundation given to the notion of social contract by two modern thinkers: Jean Jacques Rousseau and Immanuel Kant. In the text; it is pointed the revolutionary part of the notion; from showing its principal meanings and impacts. Also; reflection is made on the scope and difficulties of the contractual proposal on the contemporary democratic theory